Harnett’s Habit: Still Life Painting and Smoking Culture in the Gilded Age - Barrett, Ross (American art, 2019)
Smoking held a prominent place in William Harnett’s private experience and painterly endeavors. Between 1875 and 1880 the artist composed dozens of small-scale still lifes that foregrounded smoking products and paraphernalia, and engaged the vibrant promotional culture that arose around tobacco after the Civil War. Aiming these pictures at respectable male viewers who were, like himself, immersed in this culture, Harnett shaped complicated accounts of smoking that echoed and amplified booster imaginings of the habit, playfully undercut the brand iconographies and promotional claims of the tobacco market, and harnessed their subjects to explore a range of traditional painterly problems and still life concerns. The resulting works shed new light on Harnett’s interests in consumer culture and encourage us to reconsider the late nineteenth century within the longer history of American artistic engagements with modern commodities and advertising.